Evidence of physiotherapeutic behavior in the prevention of falls in the elderly: an integrative literature review (Research, Society and Development, 2022)
Objective: this study aims to trace the epidemiological profile of patients seen in the physiotherapy sector of a clinic - Introduction: Aging is part of a natural and physiological process, however, the elderly is also more likely to fall due to functional and visual changes and hearing, which also increases the risk of death, since falling is the most common accident among the elderly. Therefore, physical therapy treatment is very important because, through an assessment, protocols can be created to prevent falls. Objective: Search the literature for the best evidence for preventing falls in the elderly. Methodology: Refers to an integrative literature review in which a survey was conducted in the bibliography on physical therapy approaches that present the best evidence for the prevention of falls in the elderly. The databases used were PubMed, PEDro and Cochrane in the search for randomized clinical trials with scientific importance in the last five years (2016-2021). Results: A total of 345 articles were found, which, after passing the inclusion, exclusion and two stages of evaluation, left a total of 5 randomized clinical trials that were made available according to authors, title, year of publication, general objective, and main considerations. Final Considerations: The study revealed that physical exercise programs and therapy with a posturography system had better results for preventing and reducing the risk of falls in the elderly.